Centrifugal microfluidic platforms: advanced unit operations and applications. (7th October 2015) - Strohmeier, O.; Keller, M.; Schwemmer, F.; Zehnle, S.; Mark, D.; von Stetten, F.; Zengerle, R.; Paust, N.
<x xml:space="preserve">Abstract</x> Review on miniaturization, integration, and automation of laboratory processes within centrifugal microfluidic platforms. For efficient implementation of applications, building blocks are categorized into unit operations and process chains.